PERTANGGUNGJAWABAN PIDANA PELAKU PROMOSI SITUS JUDI ONLINE (JUDOL) MELALUI MEDIA SOSIAL - Maidin Gultom; Rizkinta Sembiring (Universitas Katolik Santo Thomas Medan, 2025)
This research aims to determine the criminal responsibility of perpetrators of spreading online gambling sites via social media in decisions at the Medan District Court The data used in this research is secondary data. Secondary data collection consists of data obtained from library materials, including books, the internet, statutory regulations and legal dictionaries. This empirical juridical research was carried out descriptively, logically, normatively and systematically using deductive methods. The results of the research show that the criminal liability of perpetrators of spreading online gambling sites via social media where perpetrators of spreading online gambling sites via social media is prosecuted in Article 27 paragraph (2) of Law no. 19 of 2016 concerning Amendments to Law No.11 of 2008 concerning Information and Electronic Transactions